2016
DOI: 10.1038/srep39183
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive and accurate quantification of human malaria parasites using droplet digital PCR (ddPCR)

Abstract: Accurate quantification of parasite density in the human host is essential for understanding the biology and pathology of malaria. Semi-quantitative molecular methods are widely applied, but the need for an external standard curve makes it difficult to compare parasite density estimates across studies. Droplet digital PCR (ddPCR) allows direct quantification without the need for a standard curve. ddPCR was used to diagnose and quantify P. falciparum and P. vivax in clinical patients as well as in asymptomatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
100
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(105 citation statements)
references
References 23 publications
3
100
0
Order By: Relevance
“…Our microscopy positive results had signi cantly high level of parasitaemia ranging 7000-12000 parasites/µl which resembles 0.15-0.25% quanti ed by RBC count method. Similar study was conducted by Koep i C, Nguitragool W, Hofmann NE et al had revealed light microscopy were able to quantify only upto 0.25-0.0625 µl of parasitaemia based on skilled microscopist whereas real-time PCR had quanti ed less than 0.03 µl of parasites [25].…”
Section: Discussionsupporting
confidence: 70%
“…Our microscopy positive results had signi cantly high level of parasitaemia ranging 7000-12000 parasites/µl which resembles 0.15-0.25% quanti ed by RBC count method. Similar study was conducted by Koep i C, Nguitragool W, Hofmann NE et al had revealed light microscopy were able to quantify only upto 0.25-0.0625 µl of parasitaemia based on skilled microscopist whereas real-time PCR had quanti ed less than 0.03 µl of parasites [25].…”
Section: Discussionsupporting
confidence: 70%
“…falciparum , and equal sensitivity for P . vivax compared to the previous report [37]. In the current study, the ddPCR assay was developed using duplex reactions for detection and quantification of P .…”
Section: Discussionmentioning
confidence: 99%
“…For example, the Bio-Rad ddPCR system (drop generator, PCR cycler, and reader) costs $90K-$100K, and the reagent cost per sample is ~$5. 60 By comparison, qPCR instruments are in the $25K-$50K range, and the reagent cost is $2. However, the per sample cost in qPCR may be offset by the added costs of calibration standards, whereas dPCR is calibration-free.…”
Section: Detection Of Rare Targets a Hallmark Of Dpcr Is Itsmentioning
confidence: 99%